The Effect of Profitability, Firm Size, Sales Growth and CSR Against Tax Avoidance on Companies Listed in BEI Year 2013 â 2016 - Yuli Chomsatu, Shella Octaviana, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to test the effect of profitability, firm size, sales growth and CSRon tax avoidance. This type of research in the research it is associative with thecausal relationships. This research uses the cash effectife taxes rates as a proxy oftax avoidance. The population of this research as much as 156 companies listed atthe IDX and publishes sustainability report year 2013-2016. While the sample wasselected using a purposive sampling method and retrieved samples as many as 75companies. In this study data analysis methods are used, namely multiple linearregression analysis. The data in this study in the analysis using the help of SPSS17. The results of this research show that profitability, firm size and the CSR effecton tax avoidance. While sales growth has no effect against tax avoidance.Keyword: Profitability; Firm Size; Sales Growth; CSR; Tax Avoidance.